Trabalho e organização do Arsenal de Marinha do Rio de Janeiro na década de 1820 - Karina Brotherhood (Navigator)
The Imperial Brazilian Navy had in its professional staff individuals deriving from many social groups. So, when we observe the functioning of the Armory it is also possible to study the different social profiles that lived in Rio de Janeiro in the period of the Announcement of Brazilian Independence. From intense analysis of the documentary patrimony of the Navy Archive and the National Archive, was possible to built, of descriptive form, the daily way of life, not only of the military themselves, but also of the main work power of this military establishment: the slaves. The power relations established between the military and the slaves contributed for a production of information that show reality lived by involved historical agents.